Rise of remote work across borders: opportunities and implications for migrant-sending countries - Mieriņa, Inta; Šūpule, Inese (Frontiers in Sociology, 2024)
Contact restrictions imposed during the COVID-19 pandemic have contributed to the rapid expansion of remote work. With this expansion, new opportunities arise for the typical migrant-sending countries in Central and Eastern Europe to remotely involve their diaspora in their labor market. The aim of this paper is, by using the case study of Latvia, to show the potential of cross-border remote work for alleviating human capital losses caused by emigration. We assess the main obstacles and necessary adjustments in taxes, social benefits, labor market regulation and other areas to facilitate the labor market transition and show what incentives the country can use to become a place of choice for performing remote work for the diaspora. Combining the perspectives of employers, employees and the government, this study sheds new light on the challenges and opportunities related to the rise of remote work for countries suffering from emigration. The comprehensive analysis builds on triangulating secondary data, analysis of policy documents, a survey of employers, as well as a survey and in-depth interviews with cross-border remote workers.